Ondas gravitacionais da teoria de Starobinsky-Podolsky em um espaço-tempo de fundo curvo - Oliveira, Regiley Pimenta Ramos De (2024)
This work proposes the study of gravitational waves in a curved background within the higher-order Starobinsky-Podolsky model. Using the principles of General Relativity to explain gravitational waves in a curved background, we add higher-order terms to the Einstein-Hilbert action to derive new field equations for this model. By perturbing the background metric, we obtain sixth-order equations, hence scalar fields tend to reduce this order.